1987
DOI: 10.1016/0014-5793(87)80655-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular organelle motility and membrane fusion processes in human neutrophils upon cell activation

Abstract: Release and subcellular fractionation experiments indicate that fusion of a novel tertiary granule with the plasma membrane is concomitant with human neutrophil activation. Phorbol 1Zmyristate 13-acetate (PMA) induced a respiratory burst in human neutrophils as well as a high release of gelatinase, a marker of the tertiary granule. Preincubation of neutrophils with cytochalasin E induced a partially activated or 'primed' state, in which cells were unable to generate superoxide anion, but showed a reduced laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Because MMP-9 protein is synthesized in the neutrophil early in its development and is stored in tertiary granules, very little mRNA for MMP-9 is seen in the neutrophil once it enters the circulation. 20,21 In contrast to the MMP-9 in the lymph, MMP-9 is activated in the myocardium, as demonstrated by both gelatin zymography and in situ zymography. The neutrophil is also the source of early MMP-9 appearance in the myocardium.…”
Section: Mmp-9 Levels In Vivomentioning
confidence: 98%
See 1 more Smart Citation
“…Because MMP-9 protein is synthesized in the neutrophil early in its development and is stored in tertiary granules, very little mRNA for MMP-9 is seen in the neutrophil once it enters the circulation. 20,21 In contrast to the MMP-9 in the lymph, MMP-9 is activated in the myocardium, as demonstrated by both gelatin zymography and in situ zymography. The neutrophil is also the source of early MMP-9 appearance in the myocardium.…”
Section: Mmp-9 Levels In Vivomentioning
confidence: 98%
“…Thus, neutrophils can easily be activated by chemotactic factors to secrete MMP-9 from the tertiary granules. 20,21,24 Additional or greater stimulation is required for degranulation of neutrophil primary granules, which contain the neutrophil proteases that might activate MMP-9. A greater sensitivity to chemotactic factors occurs when neu- Figure 6.…”
Section: Mmp-9 Levels In Vivomentioning
confidence: 99%
“…1C, lane 7 vs lane 8). The MMP differences between LH vs 9NC plasma could be caused by differential release of MMPs from, e.g., platelets and leukocytes, with a changed MMP content/profile depending on the anticoagulant used (6,8 ).…”
Section: To the Editormentioning
confidence: 99%
“…This recovery could be due either to the release of immature neutrophils from bone marrow or to recirculation of neutrophiis expressing lower CD45 ieveis from lung capillaries [25]. We have previously demonstrated that CD45 molecules arc stored in resting neutrophils on membranes from the readily translocatabie tertiary secretory granuies, as weli as in that from specific granules [9], and it is known that intraceilular compartmcntaiization of these organelles is regulated during neutrophil activation [26].…”
Section: Discussionmentioning
confidence: 99%